Advanced oxidation processes for sustainable wastewater treatment - Shamim, Aisha; Hamidah, Abdullah; Abid, Monis; Nayyab, Gul E; Nor Khonisah, Daud (Springer, 2026)
Water pollution led to prolonged organic pollutants, like pharmaceuticals, dyes, pesticides, and industrial chemicals, which pose a serious risk to both aquatic ecosystems and human health because of their toxicity, bioaccumulation, and resistance to natural degradation. Conventional wastewater treatment methods are often ineffective in completely removing these contaminants. To tackle this problem, advanced oxidation processes (AOPs) have evolved into promising technologies capable of transforming or mineralizing such pollutants into lower risk by-products. The review highlights a broad perspective of key AOP techniques, including ozonation, Fenton and photo-Fenton reactions, electrochemical oxidation, ultraviolet and solar photolysis, and ultrasonic irradiation. The underlying mechanisms of pollutant degradation are explained with emphasis on the formation of highly reactive hydroxyl radicals and other oxidative species. Critical factors influencing treatment efficiency, such as temperature, pH, catalyst type, and pollutant concentration, are examined. The review also highlights recent progress in catalyst development, energy efficiency, and reactor design, in combination with the adoption of renewable energy sources. Furthermore, emerging hybrid systems that combine AOPs with biological treatment or membrane filtration are discussed for their potential to enhance performance and reduce operational costs. Finally, the major challenges and future perspectives are outlined, emphasizing the environmental and technological significance of AOPs in advancing sustainable wastewater treatment.